MANAJEMEN PENINGKATAN MUTU PROGRAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH NEGERI - Murni Yanto (UNIVERSITAS BENGKULU, 2017)
The Islamic Elementary School (MIN) Dusun Curup is one of private Islamic elementary school that has central of excellence-oriented in implementing quality of learning program. In this program, it doesn’ only develop the student intelligence but also develop emotional aspect, sosial aspect, and spiritual aspect. In this study, there are research finding; 1) Policy in planning. 2) Teachers management oriented in competence and professional achievement. 3) Students management. 4) Learning management. 5) Method Management. 6) Learning resources management. 7) Media management. 8) Internal-external environment management. 9) Evaluation supervision.